Efektivitas Kontribusi Ekonomi Islam Dalam Menghadapi Pandemi Virus Corona-19 - Yuli Rahmadani Harahap; Delima Sari Lubis; Aliman Syahuri Zein (Journal of Islamic Social Finance Management, 2020)
Abstract The corona virus pandemic -19 has had a negative impact on the global economy, including Indonesia. Indonesia's economic growth is predicted to be minus 0.4%. The application of physical distancing has reduced the people's economic activity, resulting in a decrease in Aggregate Supply, which has an impact on decreasing production which can damage the smooth running of the market mechanism. This study aims to identify the appropriate contribution of Islamic economic philanthropy in the face of a pandemic. This research is a qualitative research using literature study. The research concludes that there are several contributions from Islamic economic philanthropy that are effective in overcoming the pandemic. These contributions are first, optimization of the application of social finance (distribution of ZIS funds, development of waqf fund-based infrastructure, guidance and assistance to MSMEs through qardhul hasan loans). Second, the development of Islamic financial technology for online market players to comply with sharia regulations. Keyword : Pandemic, Philanthropy, Social Finance, Financial Finance